Low-Grade Systemic Inflammation Profile, Unrelated to Homocysteinemia, in Obese Children - Emanuel V. Economou; Ariadne V. Malamitsi-Puchner; Christos P. Pitsavos; Evangelia E. Kouskouni; Ioanna Magaziotou-Elefsinioti; George Creatsas (Mediators of Inflammation)
To investigate in prepubertal obese children (POC) the profile of chronic low-grade systemic inflammation (CLGSI) and its relation to homocysteinemia, 72 POC were evaluated for serum C-reactive protein (CRP) and amyloid A (SAA) levels, both markers of CLGSI, and plasma levels of total homocysteine (tHcy), an independent risk factor for adult atherosclerosis, in comparison to 42 prepubertal lean children (PLC). The main observations in POC were higher CRP levels compared to PLC, positive association of SAA levels to CRP levels, no association of CRP or SAA levels to tHcy levels. Thus, in POC, positively interrelated to each other, elevated CRP and unaltered SAA levels reveal a unique profile of the CLGSI, not explaining homocysteinemia-induced risk for future atherosclerosis.